Association between dietary vitamin C and telomere length: A cross-sectional study - Cai, Yuan; Zhong, Yu-di; Zhang, Hao; Lu, Pei-lin; Liang, Yong-yi; Hu, Biao; Wu, Hui (Frontiers in Nutrition, 2023)
Background Currently, telomere length is known to reflect the replication potential and longevity of cells, and many studies have reported that telomere length is associated with age-related diseases and biological aging. Studies have also shown that vitamin C acts as an oxidant and free radical scavenger to protect cells from oxidative stress and telomere wear, thus achieving anti-aging effects. At present, there are few and incomplete studies on the relationship between vitamin C and telomere length, so this study aims to explore the relationship between vitamin C and telomere length. Methods This study used cross-sectional data from the National Health and Nutrition Examination Surveys (NHANES) database from 1999 to 2002, a total of 7,094 participants were selected from all races in the United States. Male participants accounted for 48.2% and female participants accounted for 51.8%. The correlation between vitamin C and telomere length was assessed using a multiple linear regression model, and the effect of dietary vitamin C on telomere length was obtained after adjusting for confounding factors such as age, gender, race, body mass index (BMI), and poverty income ratio (PIR). Results This cross-sectional study showed that vitamin C was positively correlated with telomere length, with greater dietary vitamin C intake associated with longer telomeres (β = 0.03, 95% CI: 0.01–0.05, P = 0.003). Conclusion This study shows that vitamin C intake is positively correlated with human telomere length, which is of guiding significance for our clinical guidance on people’s health care, but our study need to be confirmed by more in-depth and comprehensive other research results.